The Outcome of One-Stage Surgery (Open Reduction, Femoral Osteotomy, Pelvic Osteotomy) in the Treatment of DDH Between 1.5 and 6.5 Years in Basrah: Hasil dari Pembedahan Satu Tahap (Reduksi Terbuka, Osteotomi Femoralis, Osteotomi Panggul) dalam Pengobatan DDH Antara 1,5 dan 6,5 Tahun di Basrah - Akber, Mohamad A (Universitas Muhammadiyah Sidoarjo, 2024)
Abstract. Background: A broad range of hip developmental anomalies that may be identified at birth or develop later are included in developmental dysplasia of the hip (DDH). It involves a range of disease severity, from full hip dislocation to mild acetabular dysplasia. Methods: The study (prospective cohort) was performed at Ibn-Albettar Orthopedic Center. The period was between February 2019 to March 2024, patients with frank dislocation between 1.6 to 6.5 years were included. Exclusion criteria include those with a neuromuscular disorder, Arthrogryposis, failed previous surgery, and previous hip infection. Results: One hundred six patients were included (118 hips, 94 unilateral, and 24 bilateral), at the time of surgery the mean age was between 18 to 80 months, group A (61 hips) those less than 28 months while group B (57 hips) include those 28 months age and older. All hips underwent the same procedure which included single-stage open reduction, femoral osteotomy, and modified Salter osteotomy, and the mean follow-up was between 27-32 months. Regarding demographic data, the difference was for the age with the female and the left side most commonly affected. Conclusion: A single-stage operation consisting of open reduction, femoral osteotomy, and pelvic osteotomy yielded favorable radiological and clinical results for the treatment of DDH in patients between the ages of 1.5 and 6.5. Highlights: DDH ranges from mild dysplasia to severe hip dislocation. Prospective cohort study of 118 hips (2019–2024); single-stage surgery. Single-stage surgery showed favorable outcomes for DDH (ages 1.5–6.5). Keywords: one-stage surgery, open reduction, femoral osteotomy, pelvic osteotomy, DDH